The effectiveness of of Group Acceptance and Commitment Therapy (ACT)-Based Training on Parenting Stress and Psychological Flexibility in Mothers of Children with Autism Spectrum Disorderr - khadijeh shiralinia; hadiss ABDOLLAHI MUSAVI; Reza KHojastemehr (Ravānshināsī-i Afrād-i Istis̠nāyī, 2018)
Parents of a child with autism spectrum disorder are confronted with many challenges in raising their child. Researchers report that this families experience more parenting stress than families of other disabilities.The present study aimed to investigating the effect of using group Acceptance and Commitment Therapy (ACT)-Based Training on reducing Parenting Stress and increase Psychological Flexibility in Mothers of Children with Autism Disorder in Ahvaz. The research design was quasi-experimental with pre-test and posttest and control groups The statistical population of this study included all the Mothers of Children with autism spectrum disorder in Ahvaz. 44 mothers of children with autism spectrum disorder were selected through convenience sampling method, and then they were put into two experimental and control groups . The intervention group received group Acceptance and Commitment Therapy for 8 sessions of 90 minutes. The research of the study included Parentings Stress Inventory and Acceptance and Action second revised (AAQ-II). Acceptance and Commitment Therapy (ACT)-Based Training was performed in eight sessions in the experimental group. Data were analyzed using repeated measures analysis of variance. The results indicated the effectiveness of experimental treatment on the reduced scores of parenting stress and increase psychological flexibility in the mothers in the experimental group. Hence, this method is effective and useful to improve the mental health of this mothers.